Flux control modulation for the dual active bridge DC/DC converter - Fritz, Niklas; Rashed, Mohamed; Bozhko, Serhiy; Cuomo, Fabrizio; Wheeler, Patrick (2018)
This paper introduces a novel modulation technique for the single phase Dual Active Bridge (DAB) in which the switching frequency and transformer flux are modulated to achieve improved power transfer characteristics and reduced converter losses. By analyzing the DAB, it is noticed that in the traditional Single Phase Shift (SPS) modulation, the transformer flux linkage decreases with increasing power. The proposed Flux Control Modulation (FCM) counteracts this decrease and aims to keep the transformer utilization constant on the whole load range by a reduction in switching frequency. This has two effects: First, the reduced frequency substantially lowers switching losses and second, the power transfer characteristic of the DAB is linearized, facilitating the control of this converter. The new modulation technique is validated by simulation